The Effect of Flipbook Media on Improving Critical Thinking Skills of Grade 5 IPAS Students - Shitta Octaviana; Aan Widiyono; Muhammad Alie Muzakki (MIMBAR PGSD Undiksha, 2025)
Many teachers have not implemented the use of digital media, there are many digital media that can be used to support students' critical thinking skills, one of which is the use of flipbook media. This study aims to evaluate the effectiveness of flipbook media in improving elementary school students' critical thinking skills in Natural and Social Sciences (IPAS) subjects. This study uses a mixed method approach that combines quantitative data from pretests and posttests as well as qualitative data from learning observations and interviews with teachers. The results showed that the use of flipbooks significantly improved students' critical thinking skills, especially in terms of analyzing information and drawing logical conclusions. In addition, students also showed increased involvement in the learning process and a deeper understanding of IPAS concepts. Although some technical obstacles were found in the implementation, flipbooks have proven to be an effective and innovative learning medium. Therefore, its use is recommended to be integrated into IPAS learning in elementary schools to support the continuous improvement of critical thinking skills.